Psychology of Al-Fatiha Psychological Foundations in Spiritual Pedagogy - Najah Hanim Binti Mohd Hamidi; Hawa Khoirunnisa; Naan Naan (Syifa al-Qulub : Jurnal Studi Psikoterapi, 2022)
Basically, this discussion emphasizes the core purpose of spiritual pedagogy and themedium of the psychic dimension based on surah al-Fatiha. As we know, Psychology is the study ofscience that discusses various information about human life and symptoms related to aspects of thehuman in person at certain stages of development to recognize and respond to themselves and otherhumans in accordance with their development. As a Muslim, this obligation to learn to recognizeoneself is required to be based on the Qur'an and al-Hadith, while the Qur'an itself has providedvarious discussions about the "Self" and man with the tendencies. According to some mufassir, anyQur'an can be reviewed and understood through a psychological approach. And almost all mufassirbelieve that every verse of the Qur'an contains the meaning of education and learning for eachreader. Therefore, psychiatric discussions derived from the Qur'an are discussions needed inspiritual pedagogy. With the theme of this discussion, the author hopes that there will be increasedawareness of maintaining mental health and awareness using spiritual intelligence in every aspect oflife, especially in the field of education. The writing of this scientific paper uses qualitative referenceanalysis methods. Beginning with the discussion of the content of Surah al-Fatiha, the discovery ofstudies relevant to the definition of psycho-spiritual practically-ideologically, then affirmed throughthe author's view or understanding. In general, this discussion contains what is studied in spiritualpedagogy, especially the awareness of God and self-servitude and the medium of spirituality,namely mental health